Labour in the South East: a regional study of political culture and practices c 1931-1945 - Sellers, O (2020)
This Thesis examines how, following its near collapse in 1931, the political and ideological restructuring of Labour Party circa 1939-1945 was achieved not in the traditional, industrial northern heartlands, but within the south east among a burgeoning middle-class membership. For the south-east between the wars provided the main site for a significant spatial-temporal restructuring in the division of labour where the urban core of the region turned to light or service industries centred upon the production of consumer goods and free-time where women became the targets of collective consumption. Indeed, Labour’s south eastern membership was not only crucial to its sizeable victory in 1945, but contributed to the Party’s recovery by offering a democratic, welfarist model of socialism that could potentially appeal to both service workers or clerical/professional employees within the south-east. They succeeded in preserving a utopian vision of socialism essential to Labour’s revival as the champion of equality and solidarity during the war years.